A 12-week supplementation with quercetin does not affect natural killer cell activity, granulocyte oxidative burst activity or granulocyte phagocytosis in female human subjects - Heinz, Serena A.; Henson, Dru A.; Nieman, David C.; Austin, Melanie D.; Jin, Fuxia (British journal of nutrition, 2010)
Quercetin, a flavonoid found in fruits and vegetables, is a strong antioxidant with anti-inflammatory, antimicrobial and immune-modulating properties. The purpose of the present study was to investigate the effects of long-term quercetin supplementation on innate immune function and inflammation in human subjects. Female subjects (n 120; aged 30–79 years) were recruited from the community and randomised to one of three groups, with supplements administered using double-blinded procedures: 500 mg quercetin/d (n 38), 1000 mg quercetin/d (n 40) or placebo (n 42). Subjects ingested two soft chew supplements twice daily during the 12-week study period. Fasting blood samples were obtained pre- and post-study and were analysed for plasma quercetin, IL-6, TNF-α and leucocyte subset cell counts. Natural killer cell activity (NKCA) and lymphocyte subsets were assessed in a subset of seventy-four subjects. Granulocyte oxidative burst activity (GOBA) and phagocytosis were assessed in sixty-four subjects. Eighteen subjects had overlapping data. Quercetin supplementation at two doses compared with placebo increased plasma quercetin (interaction effect; P < 0·001) but had no significant influence on blood leucocyte subsets, plasma IL-6 or TNF-α concentration, NKCA, GOBA or phagocytosis. NKCA was inversely correlated with BMI (r − 0·25; P = 0·035) and body fat percentage (r − 0·38; P = 0·001), and positively correlated with self-reported physical fitness level (r 0·24; P = 0·032). In summary, results from the present double-blinded, placebo-controlled, randomised trial indicated that quercetin supplementation at 500 and 1000 mg/d for 12 weeks significantly increased plasma quercetin levels but had no influence on measures of innate immune function or inflammation in community-dwelling adult females.